2016
DOI: 10.1111/bph.13536
|View full text |Cite
|
Sign up to set email alerts
|

Update on melatonin receptors: IUPHAR Review 20

Abstract: Melatonin receptors are seven transmembrane-spanning proteins belonging to the GPCR superfamily. In mammals, two melatonin receptor subtypes exist -MT 1 and MT 2 -encoded by the MTNR1A and MTNR1B genes respectively. The current review provides an update on melatonin receptors by the corresponding subcommittee of the International Union of Basic and Clinical Pharmacology. We will highlight recent developments of melatonin receptor ligands, including radioligands, and give an update on the latest phenotyping res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
342
3
17

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 366 publications
(366 citation statements)
references
References 207 publications
4
342
3
17
Order By: Relevance
“…This effect is mediated by two types of melatonin receptors, well characterized in mammals by Dubocovich et al [29]. Thanks to these studies, the main types of receptors were finally distinguished and characterized: MT 1 and MT 2 (MEL1A and MEL1B or MTNR1A and MTNR1B) (review [30-32]). Both receptors are G-coupled 7-transmembrane receptors [33].…”
Section: Role Of Melatonin Receptorsmentioning
confidence: 99%
See 3 more Smart Citations
“…This effect is mediated by two types of melatonin receptors, well characterized in mammals by Dubocovich et al [29]. Thanks to these studies, the main types of receptors were finally distinguished and characterized: MT 1 and MT 2 (MEL1A and MEL1B or MTNR1A and MTNR1B) (review [30-32]). Both receptors are G-coupled 7-transmembrane receptors [33].…”
Section: Role Of Melatonin Receptorsmentioning
confidence: 99%
“…Additionally, receptor gene variants may cause receptor expression and function as well as increase the risk of disease and affect drug efficacy. Jockers et al [32] reported several nonsynonymous variants in both types of receptors; this list will be extended along with subsequent tests.…”
Section: Role Of Melatonin Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuroprotective effects of melatonin have been reported in the literature at the molecular, cellular, and tissue level in vitro and in animal models (reviewed by Mack et al [14]), to be achieved either by direct cellular scavenger mechanisms [15] or by melatonin receptor-mediated pathways [16]. At present, we have no indication or suggestion which of these or other mechanisms could be responsible for the remarkable improvement of the patient’s condition with melatonin treatment.…”
Section: Discussionmentioning
confidence: 99%